Characterizing microvoids in regenerated cellulose fibers obtained from viscose and lyocell processes - Sharma, Aakash; Sen, Debasis; Thakre, Shirish; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Regenerated cellulose fibers are among the most widely used bio-derived materials. Currently, there is great interest in transitioning from the traditional viscose process to the more environmentally friendly lyocell process for fiber production. Differences between the characteristics of viscose and lyocell fibers can be attributed to microstructural differences that arise due to differences in the processing techniques. Here, we use small-angle scattering to characterize the microvoids in regenerated cellulose fibers that might govern the onset of mechanical failure in these. In regenerated cellulose fibers, scattering of X-rays or neutrons at small angles is largely dominated by scattering from microvoids. We demonstrate that small angle X-ray scattering (SAXS) over the q range that is typical for most commercial instruments arises from Porod scattering from the microvoid surfaces, viz., the scattered intensity scales as q(-4). Therefore, it is not possible to extrapolate this data to lower q to obtain microvoid dimensions and volume fraction. We combine SAXS with medium-resolution small-angle neutron scattering to characterize the microvoids in regenerated cellulose fibers. Specifically, we compare fibers produced using the viscose process with those from the lyocell process. For both viscose and lyocell fibers, microvoids have a high aspect ratio and are elongated in the fiber direction. Also, the volume fraction occupied by the microvoids is comparable for viscose and lyocell fibers (0.04-0.05%). However, there are differences in the microvoid size: Microvoids are more highly oriented in lyocell fibers and have a larger average length and diameter compared with viscose fibers. This result might have important implications for understanding failure of these fibers.